Respuestas
Respuesta dada por:
2
Respuesta:
Hola!.
Resolver.
x^{2} - 17x + 60 = 0x2−17x+60=0
⇒xx +12+12
⇒xx -5−5
(x + 12) (x - 5) = 0(x+12)(x−5)=0
Tenemos dos soluciones.
x + 12 = 0x+12=0
x = -12x=−12
======================================================================
x - 5 = 0x−5=0
x = 5x=5
Sol: -12 y 5
Respuesta dada por:
2
Respuesta:
espero te sirva
Explicación paso a paso:
es lo que pude hacer xd
Adjuntos:
![](https://es-static.z-dn.net/files/dbc/f8db42edf568bc4e51ac61ad5901157d.jpg)
![](https://es-static.z-dn.net/files/d62/25c6cc9f84df5222b4d880ad5485c434.jpg)
![](https://es-static.z-dn.net/files/d33/2973f1b684d683d69d095b8f5065c0fd.jpg)
![](https://es-static.z-dn.net/files/d55/4a25fdd5e34f45270d868b0f9897da5e.jpg)
Preguntas similares
hace 4 años
hace 4 años
hace 4 años
hace 7 años
hace 7 años
hace 7 años
hace 8 años
hace 8 años